2020
DOI: 10.1371/journal.pone.0230354
|View full text |Cite
|
Sign up to set email alerts
|

SULF1 suppresses Wnt3A-driven growth of bone metastatic prostate cancer in perlecan-modified 3D cancer-stroma-macrophage triculture models

Abstract: Bone marrow stroma influences metastatic prostate cancer (PCa) progression, latency, and recurrence. At sites of PCa bone metastasis, cancer-associated fibroblasts and tumor-associated macrophages interact to establish a perlecan-rich desmoplastic stroma. As a heparan sulfate proteoglycan, perlecan (HSPG2) stores and stabilizes growth factors, including heparin-binding Wnt3A, a positive regulator of PCa cell growth. Because PCa cells alone do not induce CAF production of perlecan in the desmoplastic stroma, we… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 67 publications
0
11
0
Order By: Relevance
“…The oxidase SULF1 has been shown to modulate growth factor and cytokine signaling and to hold tumor suppressor activity in breast, pancreas, kidney, and hepatocellular cancer cell lines [ 41 ]. Moreover, it has been reported that SULF1is downregulated in PC, where it has been suggested to inhibit growth of PC bone metastases [ 42 ]. The role of TULP4, MKLN1, and ZNF532 in cancer is largely unknown.…”
Section: Discussionmentioning
confidence: 99%
“…The oxidase SULF1 has been shown to modulate growth factor and cytokine signaling and to hold tumor suppressor activity in breast, pancreas, kidney, and hepatocellular cancer cell lines [ 41 ]. Moreover, it has been reported that SULF1is downregulated in PC, where it has been suggested to inhibit growth of PC bone metastases [ 42 ]. The role of TULP4, MKLN1, and ZNF532 in cancer is largely unknown.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, it was also reported that the primary tumor promoted fibroblast secretion of fibronectin, which took part in the recruitment of bone marrow derived macrophages to the secondary site in liver and lung metastases (322,324,326,327). In a recent study, CAFs and TAMs were reported to interact in generating a perlecan (a heparan sulfate proteoglycan that stores and stabilizes growth factors implicated in regulation of prostate cancer cell growth) rich desmoplastic stroma at sites of prostate cancer bone metastasis (328). Indeed, the complex trilateral crosstalk among cancer cells, CAFs and M2 macrophages may activate endothelial cells and their bone marrow derived precursors to induce de novo angiogenesis and promote metastatic spread of tumor cells (238).…”
Section: The Effects On Tumor Progressionmentioning
confidence: 98%
“…Using this tri-culture, M2-like macrophages were found to increase levels of SULF1 and HSPG2 in fibroblasts, and that SULF1 can mitigate Wnt3a-driven growth signals. 334 In another example, Rebelo and colleagues developed an alginate-based tri-culture of lung cancer cells, CAFs and monocytes and demonstrated that the model creates an immunosuppressive and invasive environment that activated monocytes towards TAMs. It should be noted that the TAM-like phenotype was observed only when all three cell types were in the tri-culture.…”
Section: Reviewmentioning
confidence: 99%